MRI of the petromastoid canal in children. Issue 4 (1st August 2013) - Koral, Korgun; Vachha, Behroze; Gimi, Barjor; Zhang, Song; Ulualp, Seckin O.; Suter, Edgar; Fernandes, Neil; McMenamy, John; Booth, Timothy N.
<x xml:space="preserve">Abstract</x> Purpose To characterize the MRI features of the petromastoid canal in children with sensorineural hearing loss (SNHL) and in normal infants. Materials and Methods High resolution MRI examinations of 564 children who were evaluated for SNHL and brain MRI examinations of 112 infants who had normal studies were studied independently by two reviewers. Results In SNHL group, visibility of the PMC decreased for right and left PMC (P < 0.001). The width of the right PMC significantly decreased as age increased (P < 0.0001). There was no relation between abnormalities of membranous labyrinth and cochlear nerve and PMC visibility in children with SNHL (p > 0.05). In the normal group, the PMC visibility decreased with increasing age (right P = 0.0001, left P = 0.001). In the normal group also, as age increased, the PMC width decreased for both PMCs (right, P = 0.0006; left, P = 0.03). Conclusion The PMC is more frequently visualized in young children. Its visibility and width are not associated with abnormalities of membranous labyrinth and cochlear nerves. J. Magn. Reson. Imaging 2014;39:966–971. © 2013 Wiley Periodicals, Inc.